Pokemon adventures. 02 - Kusaka, Hidenori (Viz Media, 2020)
Pokémon Trainer Red goes missing, prompting his faithful friend Pikachu to team up with Trainer Amarillo del Bosque Verde in order to search for him. A quest of smarts, skills, and help from their friends ensues, pitting Yellow and Pikachu against the Elite Four in their mysterious headquarters on Cerise Island.